2016
DOI: 10.2967/jnumed.116.182022
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT Can Predict Survival of Advanced Hepatocellular Carcinoma Patients: A Multicenter Retrospective Cohort Study

Abstract: Barcelona Clinic Liver Cancer (BCLC) stage C hepatocellular carcinoma (HCC) consists of a heterogeneous group of patients with a wide range of survival times, requiring further prognostic stratification to facilitate treatment allocation. We evaluated the prognostic value of F-FDG uptake on PET/CT at the time of presentation in patients with BCLC stage C HCC. A total of 291 patients with BCLC stage C HCC who underwent F-FDG PET/CT between 2009 and 2010 for staging were retrospectively enrolled from 7 universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 31 publications
(42 reference statements)
2
28
0
Order By: Relevance
“…However, in line with the in vitro/in vivo data, HCCs with low Ki67 in spite of increased GLUT1 expression were correlated with increased EMT-related proteins, such as N-cadherin. These results might have an important implication in the use of 18F-FDG-PET/CT as a useful diagnostic tool for evaluating metastasis 49,53,54 . A previous study by our group found that increased 18F-FDG uptake in patients with HCC was associated with an increased frequency of metastasis 33 .…”
Section: Discussionmentioning
confidence: 81%
“…However, in line with the in vitro/in vivo data, HCCs with low Ki67 in spite of increased GLUT1 expression were correlated with increased EMT-related proteins, such as N-cadherin. These results might have an important implication in the use of 18F-FDG-PET/CT as a useful diagnostic tool for evaluating metastasis 49,53,54 . A previous study by our group found that increased 18F-FDG uptake in patients with HCC was associated with an increased frequency of metastasis 33 .…”
Section: Discussionmentioning
confidence: 81%
“…We believe the best role of [ 18 F]FDG PET‐CT in HCC is as a prognostic biomarker, where grade 3 uptake suggests a higher likelihood of progression and poorer overall survival. ( 22 ) High‐grade [ 18 F]FDG avidity may not only signal a change in metabolome but could also identify a more aggressive and invasive phenotype with a higher risk of microvascular invasion and metastatic disease. ( 8,9 ) For example, Kwee et al correlated high tumor [ 18 F]‐fluorocholine uptake with specific gene signatures and increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the 18F-FDG PET/CT technology, which can examine the status of glucose metabolism in tumor cells, is widely used for cancer diagnosis in clinical applications. Na et al reported that 18F-FDG uptake had an incremental prognostic value for overall survival in advanced HCC patients [ 33 ]. After butein treatment, owing to the decrease in HK-2, the glucose consumption and lactate production in HCC cells were significantly decreased ( Figure 2 ), resulting in the inhibition of HCC cell proliferation and anchorage-independent growth ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%